Calcium is involved in the gravitactic orientation in colorless flagellates - Richter, P (Journal of plant physiology, 2001)
The colorless flagellate Astasia longa shows a pronounced negative gravitaxis. The calcium fluorescence indicator Calcium Crimson was used to detect changes of the intracellular calcium concentration during gravitactical orientation. Astasia shows an increase of the fluorescence after a lag phase of about 10 s, a maximum after about 30 s and a decrease to the basic level within 60 s during gravitactic reorientation. The observed change in fluorescence corresponds to an almost doubling of the initial free calcium concentration. The influence of inhibitors, known to impair gravitaxis, on the calcium concentration of Astasia longa was tested. Addition of caffeine, an inhibitor of phosphodiesterase, increases, while addition of gadolinium, an inhibitor of mechanosensitive ion channels decreases the fluorescence signal. While gravitactic stimulation of caffeine-treated cells resulted in a kinetics of fluorescence intensity changes comparable to control cells the addition of gadolinium inhibited any calcium concentration change. Dynamic fluorescence imaging was used during a sounding rocket experiment (MAXUS 3 campaign). Different accelerations interrupted by microgravity intervals were applied to Astasia cells. The cells show an increase in the calcium signal upon acceleration and a decrease during the microgravity state. The results strongly reemphasize the working model of gravitaxis which is based on the activation of mechano-sensitive ion channels as one of the primary events in signal perception